2019
DOI: 10.3390/cells8070719
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Types Differ in Markers of Inflammation, Gut Barrier and in Specific Anti-Bacterial Response

Abstract: Crohn’s disease (CD), ulcerative colitis (UC) and inflammatory bowel disease (IBD) associated with primary sclerosing cholangitis (PSC-IBD), share three major pathogenetic mechanisms of inflammatory bowel disease (IBD)-gut dysbiosis, gut barrier failure and immune system dysregulation. While clinical differences among them are well known, the underlying mechanisms are less explored. To gain an insight into the IBD pathogenesis and to find a specific biomarker pattern for each of them, we used protein array, EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 78 publications
2
32
0
1
Order By: Relevance
“…Hypersensitivity is driven by peripheral and central mechanisms [42], involving the participation of the intestinal wall, spinal cord, and brain centers [43]. Nonetheless, contemporary histopathology studies in IBD patients, as well as the established murine models of intestinal inflammation, implicate a causative combination of progressive destruction of the intestinal mucosal barrier and altered mucosal immune responses [44].…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity is driven by peripheral and central mechanisms [42], involving the participation of the intestinal wall, spinal cord, and brain centers [43]. Nonetheless, contemporary histopathology studies in IBD patients, as well as the established murine models of intestinal inflammation, implicate a causative combination of progressive destruction of the intestinal mucosal barrier and altered mucosal immune responses [44].…”
Section: Discussionmentioning
confidence: 99%
“…In IBD patients, there are reductions in potentially anti-inflammatory microbes such as Bacteroidetes, Lachnospiraceae (16), and Faecalibacterium prausnitzii (31,32) alongside increases in potentially inflammatory microbes such as Proteobacteria and Ruminococcus gnavus (30,(33)(34)(35)(36)(37)(38)(39). Further, increased mucosa-associated bacteria (16,40) results in greater contact between gut microbes and immune system and leads to anti-bacterial immunity associated with IBD pathogenesis (41)(42)(43)(44)(45).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…TFF-3 is elevated in patients with severe sepsis and inflammatory bowel diseases. TFF-3 levels correlate with the activity of ulcerative colitis localized to the colonic mucosa, suggesting the site-specific upregulation of TFF-3 in inflamed colonic mucosa [24][25][26]. Moreover, it was shown that TFF-3 was associated with protective effect on intestinal tract injury in animal model of NEC via protection of excessive apoptosis by the increase of Bcl-2 and reduction of caspase-3 and Bax expression [27].…”
Section: Introductionmentioning
confidence: 99%